PERAN STRATEGIS GURU DALAM PENDIDIKAN FORMAL DAN SOSIAL MASYARAKAT: Rekonstruksi Melalui Paradigma Pendidikan Agama Islam - Harits Mafaza Ahsan; Nur Khasanah; Sopiaranti Sopiaranti (LPPM Institut Nida El-Adabi, 2026)
The strategic role of the teacher is frequently discussed as either a professional–pedagogical function or a social one, yet these two domains are rarely integrated within a single analytical framework, and studies grounded in the paradigm of Islamic Religious Education (PAI) remain scarce. This gap is pressing amid empirical indications of an Indonesian education crisis: the country’s PISA 2022 scores declined across reading (359), mathematics (366), and science (383) and rank among the lowest ever recorded, while national Teacher Competency Test (UKG) results show the majority of teachers falling below the minimum threshold. This study aims to (1) reconstruct the strategic role of the teacher by integrating the formal-educational and social domains, and (2) formulate a conceptual model rooted in the Islamic educator typology. Employing an integrative literature review with a critical-analytical approach, the study thematically analysed purposively selected scholarly sources retrieved fromGoogle Scholar, using the criteria of authority, relevance, and recency. The findings show that the teacher’s formal and social roles are not dichotomous but converge through the prophetic educator functions of murabbi, mu’allim, muaddib, and mursyid, with uswah hasanah (exemplary conduct) operating as the integrative axis. The study contributes the Prophetic-Transformative Teacher Model, which positions the teacher simultaneously as a professional educator and an agent of social transformation (da’i) oriented toward forming both a knowledge society and a moral society.